HASIL BELAJAR MENULIS KARANGAN SEDERHANA MENGGUNAKAN MEDIA GAMBAR BERSERI: (Studi Kasus di MI Mambaul Ulum Megaluh Jombang) - Nadiroh, Intan; WIRASTRA, MATINU BAYU (Abnauna: Jurnal Ilmu Pendidikan Anak, 2022)
Language skills are listed in the Outline of Learning Programs (GBPP) for teaching Indonesian, 2013 Curriculum for SD/MI levels in 2013 which states the importance of components in teaching Indonesian Thematic Subjects. As revealed by Tarigan, that the language component has 4 components, namely: listening skills, reading skills, speaking skills, and writing skills, all of which are mutually exclusive. closely related to mastery of the same material in language, namely mastery of vocabulary and grammatical structures of sentences. This classroom action research was conducted in an effort to overcome the problems mentioned above. The use of Serial Picture Media in learning about simple essay writing is expected to improve students' learning abilities in learning Indonesian. This classroom action research is designed in two cycles. Cycle 1 of action is emphasized on Learning Tools. At this stage the researcher used a textbook or worksheet as a reference in writing simple essays, while in the improvement of cycle 1 the researchers emphasized the concept introduction approach, namely the serial image media with the aim of increasing students' learning motivation. Evaluation and reflection of cycle 1 learning has been successful but not optimal, this is because the use of media/props has not been used optimally. These deficiencies will be corrected in cycle 2. In cycle 2, learning is emphasized on the optimal use of media/props. The evaluation and reflection of cycle 2 showed that learning had been optimally successful. The conclusion that can be drawn from this research is that the use of serial image media can improve students' learning abilities in writing simple essays, as well as improve students' skills and creativity in the Indonesian language learning process.